1998
DOI: 10.1021/bi9719962
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein Shows Strong Catalytic Cooperativity between the Two Nucleotide Sites

Abstract: P-Glycoprotein (Pgp) (also known as multidrug-resistance protein) contains two nucleotide binding sites, both of which are catalytic ATPase sites. The covalent reagent 7-chloro-4-nitrobenzo-2-oxa-1,3-diazole (NBD-Cl) reacts in catalytic sites, and full inactivation of ATPase activity occurs at a reaction stoichiometry of 1 mol of NBD-Cl/mol of Pgp. We show that, at reaction stoichiometry of < or = 1 mol/mol, both nucleotide sites become labeled in relatively nonselective fashion. There is therefore strong inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 29 publications
6
69
0
Order By: Relevance
“…The head-to-tail arrangement rationalizes the cooperativity in ATP hydrolysis that was observed in the maltose transporters and in human Mdr1 (Davidson et al, 1996;Senior and Bhagat, 1998). It is also consistent with earlier predictions based on sequence analysis (Jones and George, 1999) and with biochemical studies that demonstrate immediate vicinity of the P-loops and LSGGQ motifs Chen et al, 2001).…”
Section: Harnessing the Power Of Atp: Structure And Arrangement Of Thsupporting
confidence: 86%
“…The head-to-tail arrangement rationalizes the cooperativity in ATP hydrolysis that was observed in the maltose transporters and in human Mdr1 (Davidson et al, 1996;Senior and Bhagat, 1998). It is also consistent with earlier predictions based on sequence analysis (Jones and George, 1999) and with biochemical studies that demonstrate immediate vicinity of the P-loops and LSGGQ motifs Chen et al, 2001).…”
Section: Harnessing the Power Of Atp: Structure And Arrangement Of Thsupporting
confidence: 86%
“…Previous data utilizing 8-azido-ATP labeling has indicated that both NBS are capable of binding nucleotide (12,13,29). Protection of both of the two NBS by ATP from NEM labeling or NBD-Cl labeling has also been noted, showing that ATP binds to both NBS (10,28,43). In addition both NBS have been shown to be catalytic sites (8).…”
Section: Discussionmentioning
confidence: 96%
“…Our laboratory has studied the two nucleotide sites, and we have established that both are catalytic MgATP hydrolysis sites, which interact together closely (7)(8)(9)(10). Earlier, we proposed (11) a catalytic mechanism for Pgp, in which the two NBS hydrolyze MgATP alternately, and hydrolysis is coupled to drug transport from an inner-facing, higher affinity, drug-binding site to an outer-facing, lower affinity site.…”
Section: P-glycoprotein (Pgp)mentioning
confidence: 98%
“…Similarly, the ATPase activity of P-gp has previously been shown to be sensitive to the composition of the host lipid bilayer, and azidopine photolabeling experiments indicated that drug binding was not altered (35). Drugs are known to interact with the TMDs of P-gp (36)(37)(38), whereas ATP hydrolysis occurs in the cytosolic NBDs (39)(40)(41). A likely explanation for the increased potency of drugs to mediate the communication required to transmit drug binding events between the TMDs and NBDs in the sphingolipid/cholesterol-rich bilayer environment is an altered efficiency of allosteric conformational changes.…”
Section: The Kinetics Of [ 3 H]xr9576 Binding To P-gp Proteoliposomesmentioning
confidence: 99%